PENGARUH PERKEMBANGAN SEKTOR PARIWISATA TERHADAP TINGKAT PENGANGGURAN KABUPATEN/KOTA DI PROVINSI BALI - Weda, I Made Budi Satya; Dewi, Made Heny Urmila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study to analyze the influence development of tourism sector, namely number tourist visits, number of hotels, number of restaurants and number of travel agents both simultaneously and partially on the unemployment rate in Regency / City of Bali Province. This study uses panel data, which is a combination of time series data and cross-sectional data with 45 observation points. The method of data was observation with secondary data. The data analysis technique used linear regression analysis. The results that simultaneously number of tourist visits, number of hotels, number of restaurants and number of travel agents have a significant effect on unemployment rate in Regency / City Bali Province. Variable number of tourist visits has negative effect on unemployment rate in the Regency/City of Bali Province, number of restaurants has positive effect on unemployment rate in Regency/City of Bali Province, while variable number hotels and number of travel agents has no significant effect on unemployment rate in Regency/City of Bali Province.